Clomiphene citrate plus letrozole versus clomiphene citrate alone for ovulation induction in infertile women with ovulatory dysfunction: a randomized controlled trial - Pattraporn Chera-aree; Sirikul Tanpong; Isarin Thanaboonyawat; Pitak Laokirkkiat (BMC Women's Health, 2023)
Abstract Background The aim of this study was to compare the efficacy of the combination of clomiphene citrate (CC) and letrozole to that of CC alone in inducing ovulation in infertile women with ovulatory dysfunction. Methods A randomized controlled trial was conducted at a single academic medical center between November 2020 and December 2021. Anovulatory infertility females, aged 18 to 40, were evenly distributed by a computer-generated block of four into two treatment groups. A “combination group” received a daily dose of CC (50 mg) and letrozole (2.5 mg), while a “CC-alone group” received a daily dose of CC alone (50 mg). The study medications were administered on days 3 through 7 of menstrual cycle. The primary outcome was the ovulation rate, defined by serum progesterone levels exceeding 3 ng/mL at the mid-luteal phase. The secondary outcomes were ovulation induction cycle characteristics, endometrial thickness, conception rate, and adverse events. Results One hundred women (50 per group) were enrolled in the study. The mean age was not significantly different in both groups: 31.8 years in the combination group and 32.4 years in the CC-alone groups (P = 0.54). The prevalence of polycystic ovary syndrome in the combination and CC-alone groups was 48% and 44%, respectively (P = 0.841). According to intention-to-treat analysis, the ovulation rates were 78% and 70% in the combination and CC-alone groups, respectively (P > 0.05). There was no significant difference in the mean endometrial thickness or the number of dominant follicles of the groups. No serious adverse events were observed in either group. Conclusions Our study found no significant difference between the combination of CC and letrozole and CC alone in inducing ovulation in infertile women with ovulatory dysfunction in one cycle. The small number of live births precluded any meaningful statistical analysis. Further studies are needed to validate and extend our findings beyond the scope of the current study. Trial registration The study was registered at https://www.thaiclinicaltrials.org with the following number: TCTR20201108004 and was approved on 08/11/2020.